Meta Analysis the Effect of Gestational Diabetes Mellitus on Macrosomia and Sectio Caesarea - Ratna, Tantri Yunita; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: Gestational Diabetes Mellitus (GDM) is the degree of glucose intolerance that occurs during pregnancy. DMG is caused by damage to cells and insulin resistance, resulting in hyperglycemia and an increase in abnormal growth/macrosomia which causes cesarean delivery. This study aims to analyze the magnitude of the effect of DMG on the incidence of macrosomia and caesarean section with a meta-analysis study. Subjects and Method: This research is a systematic review and meta-analysis conducted using PRISMA flow diagram. Article searches were conducted through journal databases including: PubMed, Science Direct, and Google Scholar by selecting articles published in 2000-2020. The keywords used were: "gestational diabetes mellitus" OR "diabetes in pregnancy" AND macrosomiaAND "sectio caesarean" OR "perinatal outcomes" OR "pregnancy outcome". The inclusion criteria in this study were full text articles with an observational study design, articles using English, analysis using multivariate with adjusted odds ratio. Eligible articles were analyzed using Revman 5.3 app. Results: A total of 22 articles were reviewed in this study with a cohort study design. Meta-analysis of 12 articles showed that pregnant women with gestational diabetes mellitus had a 1.36 times risk of giving birth to a macrosomic baby compared to those without gestational diabetes mellitus (aOR=1.36; 95% CI=1.15 to 1.60; p<0.003), while 10 articles showed pregnant women with gestational diabetes mellitus had a 1.35 times risk for cesarean delivery than those without gestational diabetes mellitus (aOR=1.35; 95% CI=1.17 to 1.55; p<0.001). Conclusion: Gestational Diabetes Mellitus has a weak effect on macrosomia births and caesarean section.